(untitled) (Journal of Health, Population and Nutrition, 2010)
This descriptive study presents the profiles of abused female sex workers (FSWs) in Chennai, India. Of 100 abused FSWs surveyed using a structured questionnaire, severe forms of violence by intimate partners were reported by most (98%) respondents. Of the total sample, 76% experienced violence by clients. Sexual coercion experiences of the FSWs included verbal threats (77%) and physical force (87%) by intimate partners and forced unwanted sexual acts (73%) by clients. While 39% of the women consumed alcohol before meeting a client, 26% reported that their drunkenness was a trigger for violence by clients. The findings suggest that there is an urgent need to integrate services, along with public-health interventions among FSWs to protect them from violence. Recognition of multiple identities of women in the contexts of intimate relationships versus sex work is vital in helping women to stay safe from adverse effects on health. Key words: Descriptive studies; HIV; Spouse abuse; Violence; Violence against women; India DOI: 10.3329/jhpn.v28i3.5546 J HEALTH POPUL NUTR 2010 Jun;28(3):211-220